1995
DOI: 10.1095/biolreprod53.5.1178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photoperiod Before and After Birth on Puberty in Ewe Lambs1

Abstract: Previous studies have shown that exposure to long days followed by short days after 12 wk of age advances the onset of puberty in ewe lambs. The aim of this experiment was to determine whether or not puberty would be advanced by exposure of lambs to such a photoperiodic regime when the long days were given before birth and the short days immediately after birth. Ewes kept in natural photoperiod (NP) were housed on January 15 and allocated at random to one of four treatments: 1) NP/NP, natural photoperiod befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
1
0
4
Order By: Relevance
“…Autumn and summer pasture have lower quality than spring pasture (Machado et al 2005), however, this should not have been an issue with the current experiment as forage crops were grown for autumn/ winter and summer. The dam's perception of daylight length has been shown to affect growth rates in some species of animals (Thorton 1984;Stetson et al 1986;Sunderland et al 1995) and therefore cannot be eliminated as a potential effect on lamb daily growth rates. DeNicolo et al (2008c) compared the performance of the accelerated lambing system reported in the current paper and a conventional once-yearly lambing system.…”
Section: Discussionmentioning
confidence: 99%
“…Autumn and summer pasture have lower quality than spring pasture (Machado et al 2005), however, this should not have been an issue with the current experiment as forage crops were grown for autumn/ winter and summer. The dam's perception of daylight length has been shown to affect growth rates in some species of animals (Thorton 1984;Stetson et al 1986;Sunderland et al 1995) and therefore cannot be eliminated as a potential effect on lamb daily growth rates. DeNicolo et al (2008c) compared the performance of the accelerated lambing system reported in the current paper and a conventional once-yearly lambing system.…”
Section: Discussionmentioning
confidence: 99%
“…Estes dados, confirmam a sincronização dos primeiros cios no período reprodutivo específico da espécie em determinada região geográfica (SUNDERLAND et al, 1995;. …”
Section: Resultsunclassified
“…O segundo mecanismo envolve o efeito dos fatores metabólicos (SENGER, 2003;CASTELLANO et al, 2009), ambientais (SUNDERLAND et al, 1995) e sociais (SENGER, 2003;FIOL, QUINTANS;UNGERFELD, 2010) na síntese e liberação de GnRH.…”
Section: Regulação Da Puberdade Na Fêmeaunclassified
See 2 more Smart Citations